OsABCB14 functions in auxin transport and iron homeostasis in rice (Oryza sativa L.). (13th June 2014) - Xu, Yanxia; Zhang, Saina; Guo, Haipeng; Wang, Suikang; Xu, Ligen; Li, Chuanyou; Qian, Qian; Chen, Fan; Geisler, Markus; Qi, Yanhua; Jiang, De An
Summary Members of the ATP Binding Cassette B/Multidrug‐Resistance/P–glyco‐protein (ABCB/MDR/PGP) subfamily were shown to function primarily in Oryza sativa (rice) auxin transport; however, none of the rice ABCB transporters have been functionally characterized. Here, we describe that a knock‐down of OsABCB14 confers decreased auxin concentrations and polar auxin transport rates, conferring insensitivity to 2, 4‐dichlorophenoxyacetic acid (2, 4–D) and indole‐3‐acetic acid (IAA). OsABCB14 displays enhanced specific auxin influx activity in yeast and protoplasts prepared from rice knock‐down alleles. OsABCB14 is localized at the plasma membrane, pointing to an important directionality under physiological conditions. osabcb14 mutants were surprisingly found to be insensitive to iron deficiency treatment (–Fe). Their Fe concentration is higher and upregulation of Fe deficiency‐responsive genes is lower in osabcb14 mutants than in wild‐type rice (Nipponbare, NIP). Taken together, our results strongly support the role of OsABCB14 as an auxin influx transporter involved in Fe homeostasis. The functional characterization of OsABCB14 provides insights in monocot auxin transport and its relationship to Fe nutrition.